A prevalence study of vaginal candidiasis among pregnant women - Sutaria, Pooja; Cholera, Meera; Donga, Shilpa B. (International Journal of Advances in Medicine, 2019)
Background: Pregnancy is associated with specific anatomical, physiological and immunological changes that can predispose to infection and also alter the response to the disease process. Infections in pregnancy demands prompt adequate and careful management. The disease process as well as the treatment protocol may have profound effects on the outcome of pregnancy. Pregnant women frequently develop vaginal discharge which can lead to complications during pregnancy like abortions, premature birth, low birth weight and other morbidities. Some of the infections may be serious and life threatening for the mother while others may seriously jeopardize the fetus or neonate leaving the mother asymptomatic. The aim and objective of this study was based on the present study was aimed to study the prevalence of vaginal candidiasis among pregnant patients who were visited in outdoor patient’s department of Prasutitantra and Streeroga. Methods: About 135 high vaginal swabs were collected from the women who carrying 2nd and 3rd trimester of pregnancy with symptoms of vaginal infection. These samples were tested under microscopic examination and culture on Mac Conkey agar, blood agar and Sabouraud dextrose agar respectively. Colonial morphology, wet/K.O.H. preparation, gram staining, germ tube test, were carried out for identification of the isolated organisms. Results: Out of 135 samples collected, 61 (45.18%) patients were shown positive fungal infection of candidial species. The age group showing the highest number of positive candidiasis was of 20 to 25 years. Multigravida (60%) were more commonly affected than primigravida (40%) and commonly seen in third trimester (67.41%). Conclusions: Vaginal Candidiasis was common in pregnant women with more common in young adults.